2020
DOI: 10.1002/clc.23441
|View full text |Cite
|
Sign up to set email alerts
|

Mean arterial pressure is associated with the neurological function in patients who survived after cardiopulmonary resuscitation: A retrospective cohort study

Abstract: Background: About 18% to 40% of the survivors have moderate to severe neurological dysfunction. At present, studies on mean arterial pressure (MAP) and neurological function of patients survived after cardiopulmonary resuscitation (CPR) are limited and conflicted. Hypothesis: The higher the MAP of the patient who survived after CPR, the better the neurological function. Method: A retrospective cohort study was conducted to detect the relationship between MAP and the neurological function of patients who surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In our study, we found that early sustained low MAP (average MAP < 65 mmHg) predicts bad neurological outcomes. MAP is an indicator of tissue perfusion and is considered as predictor not only in traditional CPR, [7][8][9] but also in ECPR. 12 In Ryu's et al 12 study, they analyzed 95 survival ECPR patients and created a risk prediction model for neurological prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, we found that early sustained low MAP (average MAP < 65 mmHg) predicts bad neurological outcomes. MAP is an indicator of tissue perfusion and is considered as predictor not only in traditional CPR, [7][8][9] but also in ECPR. 12 In Ryu's et al 12 study, they analyzed 95 survival ECPR patients and created a risk prediction model for neurological prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] MAP <65 mmHg is also considered as the standard for inadequate tissue perfusion in traditional CPR studies. 7,21 Thus, we chose MAP 65mmHg as main blood pressure standard. Although the use of vasoactive drugs is an important factor to adjust blood pressure, a previous study showed that it had nothing to do with the neurological outcomes in CPR patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations